Squarate desymmetrisation–ozonolysis as an approach to β-substituted-α-ketosuccinates and squalestatin synthesis - Sintim, H; Valade, A; Harling, D; Hodgson, D (Elsevier, 2019)
Silylated tertiary alcohols from 1,2-addition of alkyllithiums to dialkyl squarates undergo alkene ozonolysis to give β-substituted-α-keto-β-(silyloxy)succinates. With 3-(triethylsilyloxy)butyllithium the methodology was applied to the 2,8-dioxabicyclo[3.2.1]octane core of the squalestatins. Enantioselective 1,2-addition to di-tert-butyl squarate using butyllithium or diethylzinc/Ti(iPrO)4 in the presence of chiral ligands (such as bisoxazolines or camphorsulfonamides, respectively) gave the corresponding tertiary alcohols in up to 67.5:32.5 er.